The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1021/jp209131c
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Ion-Beam Modification of Terthiophene Oligomers from Atomistic Simulations

Abstract: Ion-beam deposition on organic surfaces is a common approach to induce surface modification. Here, the difference in argon and polyatomic thiophene hyperthermal deposition on terthiophene oligomers is explored in classical molecular dynamics simulations. The forces on the atoms are determined using the second-generation reactive empirical bond order potential for hydrocarbons that is modified to include sulfur. Details of the potential fit and parametrization are provided. The simulations predict that the thio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 67 publications
(97 reference statements)
0
9
0
Order By: Relevance
“…Nevertheless, thermal transport modeling of GO with MD simulation is not attainable until an improved reactive empirical bond order potential of carbon/hydrogen/oxygen (REBO–CHO) has been developed . The REBO potential can simulate chemical bond breakage and formation by evaluating environmentally dependent bond orders . Compared with other well-known CHO potentials (e.g., ReaxFF-CHO), the unique feature of reoptimized REBO–CHO is that it can describe atomic interactions for a micrometer sized GO flake with good accuracy and low computational expense.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, thermal transport modeling of GO with MD simulation is not attainable until an improved reactive empirical bond order potential of carbon/hydrogen/oxygen (REBO–CHO) has been developed . The REBO potential can simulate chemical bond breakage and formation by evaluating environmentally dependent bond orders . Compared with other well-known CHO potentials (e.g., ReaxFF-CHO), the unique feature of reoptimized REBO–CHO is that it can describe atomic interactions for a micrometer sized GO flake with good accuracy and low computational expense.…”
Section: Introductionmentioning
confidence: 99%
“…124 Further, these transitions were applied to the catalytic oxidation of CO. A recent report by Kemper and Sinnott used classical atomistic MD to look at the deposition of terthiophene on hydrogen-terminated diamond. 125 In this report incident kinetic energies were limited to 100 eV and 50 eV to investigate the effects of ion beam energy on film polymerization. The authors concluded that at 100 eV there would be significant fragmentation of the terthiophene, but 50 eV would allow for the evolution of atomic hydrogen.…”
Section: Theoretical Studiesmentioning
confidence: 99%
“…Further, this atomic hydrogen may act a polymerization agent and increase the adherence of the terthiophene films. 125 Hase and coworkers have used computational studies to investigate the dynamics of energy transfer in the collisions of ions with surfaces. Their studies have investigated a number of molecules including peptides [126][127][128][129][130] and small molecules.…”
Section: Theoretical Studiesmentioning
confidence: 99%
“…The term r ij is the distance between atoms i and j , and b ij is the many-body, bond-order term. Additional details of the potential can be found in refs and .…”
Section: Computational Detailsmentioning
confidence: 99%
“…Here, classical MD simulations are carried out to examine the deposition of S, SH, and SC beams on amorphous PS with external kinetic energies of 25, 50, and 100 eV. The forces on the atoms in the simulations are determined using the second-generation reactive empirical bond-order (REBO) potential for hydrocarbons that has recently been extended to include sulfur for the short-ranged interactions and a Lennard-Jones (LJ) potential for long-ranged interactions. This potential predicts the breaking and formation of chemical bonds through analysis of the instantaneous local environment of the atoms within the system.…”
Section: Introductionmentioning
confidence: 99%